2008
DOI: 10.1590/s1413-86702008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Survival of AIDS patients and characteristics of those who died over eight years of highly active antiretroviral therapy, at a referral center in northeast Brazil

Abstract: Introduction of highly active antiretroviral therapy has resulted in a significant reduction in morbimortality and significant changes in the causes of death among HIV/AIDS patients. For this reason, it has become essential to monitor survival and causes of death. We constructed a survival curve based on 597 adult patients notified as AIDS cases between 1997 and 2004, at the Hospital das Clínicas, Federal University of Pernambuco, Recife, Brazil. Among those patients, 150 (25%) progressed to death by December,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
11
1
3
Order By: Relevance
“…Assim, o ano da introdução do esquema HAART (1996) parece ser um marco significativo, e tem sido utilizado como divisor de águas para esse aumento de sobrevida 8 , e a consequente mudança na evolução da epidemia 9 . Tendo em vista a necessidade de controle das doenças transmissíveis, dados de vigilância epidemiológica (VE) têm-se constituído em uma fonte de informações importante para avaliação do curso de epidemias e endemias.…”
Section: Introductionunclassified
“…Assim, o ano da introdução do esquema HAART (1996) parece ser um marco significativo, e tem sido utilizado como divisor de águas para esse aumento de sobrevida 8 , e a consequente mudança na evolução da epidemia 9 . Tendo em vista a necessidade de controle das doenças transmissíveis, dados de vigilância epidemiológica (VE) têm-se constituído em uma fonte de informações importante para avaliação do curso de epidemias e endemias.…”
Section: Introductionunclassified
“…generally at a late stage and with advanced immunosuppression. 18,19 Failures of post-test counseling to convey the benefits of early medical follow-up, or difficulties in accessing medical care are important factors in the previously described disparity between the time of diagnosis at the VCT and the presentation for medical care in Brazil. 11 There was no great variation in viral subtypes found between recent and chronic infections, with predominance of subtype B followed by subtype F. Differing from the southern region of the country, the frequency of subtype C remained low in both groups (less than 5%).…”
Section: Discussionmentioning
confidence: 99%
“…That association has been described in previous reports, even though authors have found contradictory results. Lower mortality for women was reported in studies conducted in Brazil 9 and in African and Asian countries 13 . In contrast, women were found to have shorter survival in the follow-up of a cohort from Rio de Janeiro, Brazil 7 .…”
mentioning
confidence: 87%
“…This is the case of survival analysis, which has been performed on whole-country health surveillance databases 5,6 or with follow-up of cohorts from large cities [7][8][9][10] . These studies report longer survival times for men that have sex with men (MSM) and patients admitted without AIDS-defining conditions.…”
mentioning
confidence: 99%